Thromboprophylaxis with enoxaparin is associated with a lower death rate in patients hospitalized with SARS-CoV-2 infection. A cohort study. (October 2020) - Albani, Filippo; Sepe, Lilia; Fusina, Federica; Prezioso, Chiara; Baronio, Manuela; Caminiti, Federica; Di Maio, Antonella; Faggian, Barbara; Franceschetti, Maria Elena; Massari, Marco; Salvaggio, Marcello; Natalini, Giuseppe
Abstract: Background: Severe Acute Respiratory Syndrome CoronaVirus 2 (SARS-CoV-2) infection is associated with hypercoagulability caused by direct invasion of endothelial cells andproinflammatory cytokine release. Thromboprophylaxis with enoxaparin is recommended by current guidelines, but evidence is still weak. The aim of this study was to assess the impact of thromboprophylaxis with enoxaparin on hospital mortality in patients admitted for Coronavirus disease 2019 (COVID-19). The effects of enoxaparin on intensive care admission and hospital length-of-stay were evaluated as secondary outcomes. Methods: Observational cohort study, with data collected from patients admitted to Poliambulanza Foundation with positive real time reverse transcription polymerase chain reaction (RT-PCR) for SARS-CoV-2 from 20th February to 10th May 2020. Multivariate logistic regression with overlap weight propensity score was used to model hospital mortality and intensive care admission, hospital length-of-stay was analyzed with a multivariate Poisson regression. Seven hundred and ninety nine (57%) patients who received enoxaparin at least once during the hospitalization were included in the enoxaparin cohort, 604 (43%) patients who did not were included in the control cohort. Findings: At the adjusted analysis enoxaparin was associated with lower in-hospital mortality (Odds Ratio 0·53, 95% C.I. 0·40–0·70) compared with no enoxaparin treatment. Hospital length-of-stay was longer for patients treated with enoxaparin (Incidence Rate Ratios 1·45, 95% C.I. 1·36–1·54). Enoxaparin treatment was associated with reduced risk of intensive care admission at the adjusted analysis (Odds Ratio 0·48, 95% C.I. 0·32–0·69). Interpretation: This study shows that treatment with enoxaparin during hospital stay is associated with a lower death rate and, while results from randomized clinical trials are still pending, this study supports the use of thromboprophylaxis with enoxaparin in all patients admitted for COVID-19. Moreover, when enoxaparin is used on the wards, it reduces the risk of Intensive Care Unit admission.